Positivismo jurídico e hermenêutica: a busca do justo - Sales, Patrícia (2020)
The purpose of this paper is, after analyzing the concepts of jusnaturalism, legal positivism, post-positivism, hermeneutics, interpretation and the question of justice, to demonstrate that the legal operators have all the necessary instruments to deal with the legal system in a way that allows it to achieve its greater objective: the justice. All the activity of the legal expert will be under the analysis, covering the stricto sensu interpretation, integration, construction, creation of the system in opposition to the theory of mechanistic interpretation, supported by legal positivism, which highlights the declarative element about the productive or creative in law